APPLICATION OF UNCONDITIONAL POSITIVE REGARD IN A HUMANISTIC APPROACH TO GUIDANCE AND COUNSELING SERVICES TO IMPROVE STUDENTS' LEARNING MOTIVATION AT MAN 1 BIMA CITY - Mutahidah, Ulfatul; M. Eikal Desta Pratama; Nurrahmania; Abi Qurahman; Nur Hayatun Nufus; Nur Aulia (Jurnal Ilmiah Konseling Pendidikan, 2026)
This study aims to examine the application of Unconditional Positive Regard within a humanistic approach in guidance and counseling services to improve students' learning motivation at MAN 1 Bima City. This study uses a descriptive qualitative method. The research subjects consisted of guidance and counseling teachers and students who had participated in counseling services. Data were collected through in-depth interviews, observations, and field notes. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing, using source triangulation to ensure data validity. The results show that the application of Unconditional Positive Regard by guidance and counseling teachers is implemented through empathy, unconditional acceptance, warm communication, and non-judgmental attitudes toward students. Guidance and counseling teachers are open and friendly in listening to students’ problems, which helps create a positive psychological relationship. The application of this approach makes students feel valued and accepted, especially since the teachers use the lesehan concept in providing counseling services. The impact of implementing Unconditional Positive Regard can be seen in changes in students’ learning attitudes, such as increased discipline in attending school, reduced truancy, and greater student engagement in completing learning assignments. Thus, the implementation of Unconditional Positive Regard within a humanistic approach in guidance and counseling services can improve students' learning motivation at MAN 1 Bima City.